Pembuktian Dan Alat Bukti Pengakuan Perspektif Fuqaha Dan Hukum Perdata - Baso Muhammad Nibras; Sukmawati Markun; Asni; Abd Halim Talli (Yayasan Azhar Amanaa Yogyakarta, 2026)
Evidence is a fundamental element in dispute resolution, both from an Islamic and civil law perspective, as it serves as the basis for judges to establish certainty about the truth of a legal event before rendering a verdict. One form of evidence that holds a crucial position in both legal systems is confession (*al-iqrār*). This study aims to analyze the concept of proof, the status of confession evidence from the perspective of jurists and Indonesian civil law, and its relevance in the Indonesian judicial system. This study employed library research with a qualitative approach. Data were obtained from fiqh books, books, scientific journals, laws and regulations, and other relevant scientific sources. The results indicate that proof in Islamic law has a normative basis derived from the Qur'an and the Hadith, while Indonesian civil law regulates confession as evidence in Article 164 of the HIR and Article 1866 of the Civil Code. Islamic jurists agree that a confession has high evidentiary value if it is made by a legally competent party, voluntarily, and against a clear object. Conversely, civil law places greater emphasis on the legal consequences of a confession in the evidentiary process. Despite differences in philosophical foundations and application requirements, both legal systems place confessions as a crucial form of evidence in achieving legal certainty and justice.